Outage Probabilities of Wireless Systems With Imperfect Beamforming - Li, H.; Yu-Dong Yao; Jin Yu (IEEE transactions on vehicular technology, 2006)
This paper investigates the outage probability of a wireless system with conventional beamforming using a uniform linear array beamformer. The focus is to examine the impact of beamforming impairments, such as direction-of-arrival (DOA) estimation errors, signal spatial spreads, antenna array perturbation, and mutual coupling. Fading statistics of Rayleigh, Rician, and Nakagami are used to characterize the desired signal, whereas interferers are assumed to be subject to Rayleigh fading. A simplified beamforming model is used in deriving closed-form outage probability expressions. Numerical results illustrate the increase of outage probabilities in the presence of DOA estimation errors, signal spatial spreads, and antenna perturbation. However, negligible outage performance impact is observed due to mutual coupling